EFL Students’ Perception on Blended Learning amidst COVID-19 Pandemic - Izzulhaq, Novyansyah Ilyas; Meiristiani, Noeris (LPPM Universitas Pancasakti Tegal, 2021)
During the Covid-19 pandemic, blended learning became an alternative way to conduct teaching. To evaluate the implementation of blended learning, this research aimed to collect students’ perception and to know the implementation and the extent of blended learning. It used descriptive analysis design and qualitative approach. The research took place at SMK Muhammadiyah 1 Kota Tegal with an English teacher and 40 students from third grade as the participants. The teacher was interviewed to collect data on the implementation and the extent of blended learning and the students were questionnaires to share their perception on the blended learning. The results showed that SMK Muhammadiyah 1 Kota Tegal implemented anchor-blend type of blended learning since early 2021. Based on the students’ perception, the implementation of the blended learning is not effective during online session. Students gave positive tendency on learning flexibility, offline session, students’ interaction and students’ motivation. However, students gave negative tendency on online session and learning management.